DEAD-box helicase 56 functions as an oncogene promote cell proliferation and invasion in gastric cancer via the FOXO1/p21 Cip1/c-Myc signaling pathway. Issue 5 (2nd May 2022) - Wang, Jiancheng; Wang, Ye; Wang, Junfu; Zhang, Siwen; Yu, Zhu; Zheng, Kaitian; Fu, Zhao; Wang, Congjun; Huang, Weijia; Chen, Junqiang
ABSTRACT: DEAD-box helicase (DDX) family exerts a critical effect on cancer initiation and progression through alternative splicing, transcription and ribosome biogenesis. Increasing evidence has demonstrated that DEAD-box helicase 56 (DDX56) is over-expressed in several cancers, which plays an oncogenic role. Till the present, the impact of DDX56 on gastric cancer (GC) remains unclear. We conducted high-throughput sequencing (RNA-seq) to demonstrate aberrant DDX56 levels within 10 GC and matched non-carcinoma tissue samples. DDX56 levels were detected through qRT‐PCR, western blotting (WB) and immunochemical staining in GC patients. We conducted gain- and loss-of-function studies to examine DDX56's biological role in GC development. In vitro, we carried out 5‑Ethynyl‑2‑deoxyuridine (EdU), scratch, Transwell, and flow cytometry (FCM) assays for detecting GC cell growth, invasion, migration and apoptosis. Additionally, gene set enrichment analysis (GSEA), WB assay, and Encyclopedia of RNA Interactomes (ENCORI) were carried out for analyzing DDX56-regulated downstream genes and signaling pathways. In vivo, tumor xenograft experiment was performed for investigating how DDX56 affected GC development within BALB/c nude mice. Functionally, DDX56 knockdown arrested cell cycle at G1 phase, invasion and migration of AGS and MKN28 cells, and enhanced their apoptosis. Ectopic DDX56 expression enhanced the cell growth, migration and invasion, and inhibited apoptosis. Knockdown of DDX56 suppressed GC growth in the tumor models of BALB/c nude mice. Mechanistically, DDX56 post-transcriptionally suppressed FOXO1/p21 Cip1 protein expression, which could activate its downstream cyclin E1/CDK2/c-Myc signaling pathways. This sheds lights on the GC pathogenic mechanism and offers a potential anti-cancer therapeutic target. ABSTRACT: uf0001